The effect of bleaching agent on the compressive strength of orthodontic thermoplastic retainer materials - Ailin Ehteshami (Dental Research Journal)
Background: There is an increasing desire for teeth bleching after orthodontic treatment. Therefor, this study aims to evaluate the effect of carbamide peroxide 15% and thermocycling on the compressive strength of polyethylene terephthalate glycol (PETG) thermoplastic retainer material. Materials and Methods: In this in vitro study, forty samples of PETG material were thermoformed over a plastic template (10 mm × 8 mm × 2 mm). The samples were divided into four groups, with ten samples in each group. Group I served as the control, Group II was exposed to carbamide peroxide 15% (5 h daily for 14 days), Group III underwent thermocycling (5000 times), and Group IV underwent thermocycling (5000 times) followed by exposure to carbamide peroxide 15% (5 h daily for 14 days). The compressive strength of the groups was then evaluated using one-way ANOVA and Tukey’s HSD tests for statistical analysis. The significance level was set to 0.05. Results: The analysis showed a significant difference among the four groups. The compressive strength of all groups significantly decreased compared to the control group. Group II exhibited a significant decrease compared to Group III (P = 0.003). However, there was no significant difference between Group II and Group IV (P = 0.191). In addition, there was no significant difference observed between Group III and Group IV (P = 0.308). Group II had the lowest compressive strength (163.9 Mpa). Conclusion: It is not recommended to use a thermoplastic retainer as a bleaching tray during the initial phase of retention. However, since there were no further harmful effects of bleaching agents observed after thermocycling, it is possible to recommend the use of a thermoplastic retainer as a bleaching tray toward the end of the retention phase.